Bioaccumulation and elimination of waterborne mercury in the midge larvae, Chironomus riparius Meigen (Diptera: Chironomidae) - Azevedo-Pereira, Henrique M. V. S. (2019)
Here, mercury kinetics and behavioural effects in the midge larvae under a water-only exposure were assessed. Uptake and elimination of waterborne mercury were described by using a one-compartment kinetic model. Results show that midges were able to readily accumulate the heavy metal (BCF = 450), presenting a fast uptake, up to 13.1 μg Hg g of animal(-1) at the end of the exposure period. Elimination was slow, with c.a. 39 % of the mercury in larvae being depurated after 48 h in clean medium. Behaviour did not present differences upon exposure or elimination, but a trend to increase ventilation was noticed during the exposure period.